Pengembangan Model Penerimaan Website eCommerce pada Pelaku UMKM berbasis Teori Penerimaan Teknologi - faradillah, faradillah; Muhammad Fadhiel Alie (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
This research aims to develop a model and theory of technology acceptance so that it can then be used to measure the level of technology acceptance of society/people towards innovation and existing technology in an effort to optimize ongoing business processes in an organization. In this research, several variables identified as being able to support the application of technology were used as constructs in developing existing acceptance models, namely: TAM, IDT and ECT. The results of testing the inner and outer models show significant results for almost all the predictions that have been built. Apart from that, all the proposed constructs have also been proven empirically to be valid and reliable in building this development model. Other aspects such as community culture, environment, IT infrastructure can then be studied more deeply and become additional constructs for similar research.